Investigating Creative Prowess of Senior High School Students in Visual Communication: Case Study of Grade ‘A’ Girls’ School in Ghana - Agyarkoh, Dr. Eric; Appiah, Dr. James Ekow; Banfo, Mr. Frederick (African Journal of Education,Science and Technology (AJEST), 2024)
This paper used school-based art competition to identify Senior High School Visual Art and non-Visual Art students who revived or repressed artistically in Junior High School). Artistic revival is when children who have talent and interest in drawing continue to draw and paint after age 13 and 14, whiles artistic repression is when children who lack special skills in drawing redraw from drawing and painting from age 13 upwards (Lowenfeld & Brittian, 1982). The paper also investigated factors that influenced the students in selecting their programmes in Senior High School. The study was rooted in the interpretivism paradigm and used qualitative research approach and case study research design. Purposive sampling technique was used to select 135 students of a grade ‘A’ Girls’ Senior High School in the Cape Coast metropolis, Ghana to participate in the art competition. Interview guide, scoring keys and still-picture photography were used to gather qualitative data from the drawings and paintings of the participants. Aesthetic appreciation was used to analyse ten best paintings that emerged from the competition and the post-art competition interview data was analysed thematically. The findings of the analysis revealed that, all the non-Visual Art students who participated in the art competition revived in drawing in Basic School but they were compelled by their parents or guardians to offer other programmes in Senior High School other than Visual Art. Also, some of the Visual Art students who participated in the art competition repressed in drawing in basic school. The findings also indicated that, Basic and Senior High School head teachers, teachers and friends encourage students with high drawing and academic aptitudes to offer Science, Business, General Arts and other programmes instead of Visual Arts. Based on the findings, the study recommends that, basic school head teachers and teachers, high school head teachers and teachers, students and parents must be oriented about the dangers of diverting highly creative persons natural orientations into non-Creative Arts programmes and professions. Also, Ghana Education Service must identify Basic School candidates who have exceptional talents in art and place them in Senior High School Visual Art programmes, and Visual Art departments in tertiary institutions must revise their entry requirements to include students from other programmes who have special skills and interest in drawing and painting.